Stressors are Correlated with the Development of Conversion Disorder Presenting with Non-epileptic Events (Medicine Today, 2020)
Introduction: To study the socio-demographic and psychosocial correlates in patients with conversion disorder presentingwith nonepileptic events and discuss its interventional implication.Materials and Methods: This cross-sectional descriptivestudy was carried out in a tertiary care hospital of BrahmmanBaria Medical College from January 2018 to January2019. 151 consecutive patients with conversion disorder satisfying the inclusion and exclusion criteria were selected. Theywere interviewed using semi-structured socio-demographic profile proforma, Holmes and Rahe stress scale for the explorationof psycho-social stressors. The data were entered on MS excel, analyzed by SPSS-version 16.0.Results: The psychosocialstressors were clearly identified in all patients. Almost ninety five (94.70%, n=143) out of the total 151 subjects hada history of stressors, while in the rest 4.95% no stressors could be established. The commonest stressors were Troubleswith in-laws (26.49%), Death of close family member (11.92%) and Increase in argument with significant others (10.59 %).Conclusion: Significantly higher number of the patients presented with the stressor of troubles with in-laws, when assessedon the Holmes and Rahe Social Readjustment Rating Scale. Detection of exact nature of correlates has immense potentialfor therapeutic as well as preventive field.Medicine Today 2020 Vol.32(2): 134-137